Olak pool capacity study on ameroro dam overflow building - Sukma Ma’ri Fatullah; Ratna Musa; Ali Mallombasi; Mas’ud SAR (Jurnal Scientia, 2024)
Dams, constructed using various materials such as earth fill, stone fill, concrete, and/or stone masonry, serve the primary function of water storage. However, they can also be designed to retain sediment, forming reservoirs. Central to dam infrastructure is the spillway, tasked with regulating water release downstream. This research aims to assess the magnitude of outflow discharge by conducting flood tracing calculations through the spillway and evaluating the effectiveness of stilling ponds in channeling design flood discharge at Ameroro Dam. Employing HEC-RAS for stilling pond modeling, the study reveals that the stilling pond effectively manages flood discharges corresponding to Q100, Q1000, and QPMF events. Analysis using HEC-RAS further indicates that while the stilling pond adequately handles flow conditions during the Q100 return period, it proves ineffective in reducing the flow from the launch channel. Notably, the resulting Froude number of 6.40 signifies supercritical flow, prompting the inclusion of a beacon at the end sill. Consequently, the modified stilling pond configuration reduces flow velocity, transitioning the launch channel flow to subcritical with a Froude value of 0.18.